The Islamic Dialectics and Local Culture in The Petawaren Tradition in Gayo Community - Marhamah Rusdy; Fauzi Fauzi (UIN Maulana Malik Ibrahim Malang, 2020)
This research aims to analyze the rituals or practices as well as traditional objects used in the Petawaren tradition of the Gayo community in Central Aceh District. This research is descriptive research using a qualitative approach. The data needed are the ritual or implementation of Petawaren tradition and the traditional objects used, especially at a wedding or Ngerje ceremony. Primary data are obtained from research informants, namely traditional leaders, cultural figures, and community leaders, while secondary data are obtained from the relevant literature, documents, results of previous studies, and references. The techniques of collecting data are done by interviewing, observing, and documenting. This research also employs a relational dialectical theory. The results conclude that Petawaren tradition is purely Gayo culture, whereas the dialectics of Islam and Petawaren tradition in the Gayo community is more like accommodation of Islamic values. Therefore, the interpretation of the customary symbols, practices, and objects is eventually based on the Islamic teachings which replace the animistic beliefs existing before the arrival of Islam. Penelitian ini bertujuan menganalisis ritual (amalan) serta benda-benda adat yang digunakan dalam pelaksanaan tradisi Petawaren masyarakat Gayo di Kabupaten Aceh Tengah. Penelitian ini merupakan penelitian deskriptif yang menerapkan pendekatan kualitatif. Data yang diperlukan berupa tata cara pelaksanaan serta benda-benda yang digunakan dalam tradisi Petawaren pada upacara perkawinan Ngerje. Data utama bersumber dari informan penelitian, yaitu sesepuh (petue), tokoh adat, dan tokoh masyarakat. Sedangkan data sekunder diperoleh dari literatur, dokumen, hasil penelitian terdahulu, dan referensi yang relevan. Teknik pengumpulan data dilakukan dengan wawancara, pengamatan, dan dokumentasi. Penelitian ini menggunakan pendekatan teori dialektika relasional. Hasil penelitian menyimpulkan bahwa tradisi Petawaren adalah murni budaya Gayo, sedangkan dialektika Islam dan tradisi Petawaren pada masyarakat Gayo lebih kepada akomodasi nilai-nilai Islam. Oleh karena itu, pemaknaan terhadap simbol-simbol, ritual (amalan), dan benda-benda adat pada akhirnya didasarkan pada ajaran Islam, menggantikan kepercayaan animisme yang ada sebelum Islam datang.